Analysis of low-cost electronic device for diagnosis of COVID-19. (28th December 2021) - Bhati, Akshaya Nidhi; Maharshi, Himanshu; Kumar, Arun
This paper presents the design of a low-cost electronic device that can be used to diagnose coronavirus disease 2019 (COVID-19) at home with the help of symptoms. The device will check whether the patient has a fever or not with the help of a thermal sensor, oxygen saturation in the blood (Spo2) with the help of a pulse-oximeter, and cough through artificial intelligence. The remaining symptoms will be diagnosed using a survey-based system, where respondents will be invited to self-report various symptoms. The estimate, conception and development of this device can greatly contribute to the creation, and assist in breaking off the spread of the disease, getting the timely treatments and potentially save lives.